The way things go - Fischli, Peter; Weiss, David, 1946-; Richterich, Alfred; Corradi, Pio, 1940-; First Run/Icarus Films; First-Run Features (Firm); T & C Film AG. ([New York, NY] : First Run/Icarus Films, 2002)
The Swiss artists Peter Fischli and David Weiss harness air, water, fire, chemical reagents and simple machines to enact a chain of events that becoms an endlessly inventive meditation on cause and effect generating continuous process.
Originally produced by T&C Film AG & Alfred Richterich, c1987.
Title from DVD title screen.
"A First Run Features presentation"--Beginning fr.
DVD features: newly re-mastered, biographies, bibliography, scene access, interactive menus.
DVD accompanied by: 2002 DVD catalog, the best in independent, foreign, fiction & documentary DVD / First Run Features. [New York : First Run Features, 2002].
Camera, Pio Corradi.
Keywords: Performance art -- Switzerland; Artists -- Switzerland -- 20th century; Arts, Modern -- 20th century